Pengaruh Pendekatan Pembelajaran Mendalam Dan Model Mengajar Berbasis Masalah Terhadap Karakter Murid Kelas XI Dalam Pembelajaran PAK di SMA Negeri 1 Pahae Julu Tahun Pembelajaran 2025/2026 - Fransisca Hasugian; Hisardo Sitorus; Betty Arli Sonti Pakpahan (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The purpose of this study was to determine and analyze 1) the effect of a partial in-depth learning approach on the character of class XI students in PAK learning at SMA N 1 Pahae Julu; 2) the effect of a partial problem-based teaching model on the character of class XI students in PAK learning at SMA N 1 Pahae Julu; and 3) the effect of a simultaneous in-depth learning approach and problem-based teaching model on the character of class XI students in PAK learning at SMA N 1 Pahae Julu. The method used in this study is an inferential quantitative method. The population is all class XI students of SMA Negeri 1 Pahae Julu in the 2025/2026 academic year who are Protestant Christians totaling 141 students and a sample of 104 people was determined using a simple random sampling technique. The instrument trial was conducted on 37 people outside the research sample so that it was known that all research instruments were declared valid and reliable because they had met the validity and reliability value criteria. Data were collected with a closed questionnaire of 70 items. The results of the data analysis show that: 1) the Fcount value > Ftable is 70.629 > 3.07, thus it is known that there is a positive and significant influence of the application of the deep learning approach on the formation of student character in PAK learning. The influence is 40.9%, 2) the Fcount value > Ftable is 45.597 > 3.07, thus it is known that there is a positive and significant influence of the application of the problem-based learning model on the formation of student character in PAK learning. The influence is 30.9%, and 3) the Fcount value > Ftable is 41.673 > 3.07, thus it is known that there is a positive and significant influence simultaneously between the deep learning approach and the problem-based learning model on the formation of student character in PAK learning. The influence is 45.2%, thus Ha is accepted and H0 is rejectedThe purpose of this study was to determine and analyze 1) the effect of a partial in-depth learning approach on the character of class XI students in PAK learning at SMA N 1 Pahae Julu; 2) the effect of a partial problem-based teaching model on the character of class XI students in PAK learning at SMA N 1 Pahae Julu; and 3) the effect of a simultaneous in-depth learning approach and problem-based teaching model on the character of class XI students in PAK learning at SMA N 1 Pahae Julu. The method used in this study is an inferential quantitative method. The population is all class XI students of SMA Negeri 1 Pahae Julu in the 2025/2026 academic year who are Protestant Christians totaling 141 students and a sample of 104 people was determined using a simple random sampling technique. The instrument trial was conducted on 37 people outside the research sample so that it was known that all research instruments were declared valid and reliable because they had met the validity and reliability value criteria. Data were collected with a closed questionnaire of 70 items. The results of the data analysis show that: 1) the Fcount value > Ftable is 70.629 > 3.07, thus it is known that there is a positive and significant influence of the application of the deep learning approach on the formation of student character in PAK learning. The influence is 40.9%, 2) the Fcount value > Ftable is 45.597 > 3.07, thus it is known that there is a positive and significant influence of the application of the problem-based learning model on the formation of student character in PAK learning. The influence is 30.9%, and 3) the Fcount value > Ftable is 41.673 > 3.07, thus it is known that there is a positive and significant influence simultaneously between the deep learning approach and the problem-based learning model on the formation of student character in PAK learning. The influence is 45.2%, thus Ha is accepted and H0 is rejected